Pengaruh Kualitas Produk, Brand Image dan Store Atmosphere terhadap Keputusan Pembelian Konsumen pada Restoran Bale Udang Mang Engking Kuta - Ni Kadek Ayu Suciati; I Nengah Wirsa (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study examines the influence of product quality, brand image, and store atmosphere on consumer purchasing decisions at Bale Udang Mang Engking Kuta. The research was conducted at the restaurant using a purposive sampling technique with 144 respondents who met the criteria of having visited the restaurant and being at least 17 years old. Primary data were collected through a Likert-scale questionnaire, which was tested for validity and reliability prior to analysis using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through SmartPLS 4.0. The results show that the model has strong explanatory power (R² for purchasing decisions = 0.750). Partially, product quality has a positive and significant effect on purchasing decisions (coefficient = 0.339; t = 4.406; p = 0.000), brand image has a positive and significant effect (coefficient = 0.281; t = 3.356; p = 0.001), and store atmosphere also has a positive and significant effect (coefficient = 0.333; t = 3.508; p = 0.000). These findings confirm that improvements in product quality, the strengthening of brand image, and the creation of an appealing store atmosphere collectively enhance consumer purchasing decisions at Bale Udang Mang Engking Kuta. The practical implication of this study suggests that the restaurant’s management should maintain product freshness and taste consistency, reinforce brand uniqueness, and regularly update and maintain the physical environment and ambiance to sustain and increase consumer purchasing decisions.